Manajemen Laba, Kepemilikan Institusional, dan Kinerja Keuangan: CSR sebagai Variabel Moderasi - Ananda Laksmita Dewi; Imam Ghozali (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2023)
ABSTRACTThis study aims to examine the effect of earnings management and institutional ownership on financial performance moderated by CSR. The sample is 16 companies that have been listed on the Indonesia Stock Exchange in 2017-2021 with purposive sampling technique. Data sourced from Bloomberg. The data analysis technique of this study uses the Partial Least Square (PLS) approach. The results of the study show that earnings management and institutional ownership have a positive effect on financial performance, CSR is not able to moderate the relationship between earnings management and financial performance, and CSR strengthens the relationship between institutional ownership and financial performance.Keywords: Earnings management, institutional ownership, financial performance, CSRÂ ABSTRAKStudi ini memiliki tujuan untuk menguji efek dari manajemen laba dan kepemilikan institusional terhadap kinerja keuangan dengan dimoderasi oleh CSR. Sampel sebanyak 16 perusahaan yang telah terdaftar pada Bursa Efek Indonesia tahun 2017-2021 dengan teknik purposive sampling. Data bersumber dari Bloomberg. Teknik analisis data studi ini memakai pendekatan Partial Least Square (PLS). Hasil studi menunjukkan manajemen laba dan kepemilikan institusional berpengaruh positif terhadap kinerja keuangan, CSR tidak mampu memoderasi hubungan antara manajemen laba dan kinerja keuangan, serta CSR memperkuat hubungan antara kepemilikan institusional dan kinerja keuangan.Â Kata Kunci: Manajemen laba, kepemilikan institusional, kinerja keuangan, CSRÂ